RELASI KERJA PEREMPUAN PENDULANG EMAS DI DESA LOGAS KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Meileni Candra Putri; Rina Susanti (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Kuantan Singingi Regency is believed to be a gender-responsive village model in the Small-Scale Gold Mining (PESK) sector, the only one in Indonesia, where more than 204 women participate in the PESK sector. The purpose of study is to analyze the work activities and the forms of work relations among the gold-panning women with gold boss (tauke) using Social Exchange and Rational Choice theories. The research took place in Logas Kuantan Singingi village using qualitative methods through observation, interviews, documentation and triangulation being the data collection techniques. This study found that the work activities of gold-panning women began with preparing work tools, moving to the work site, panning for gold, separating gold and selling gold. The working relations established between gold-panning women and gold boss include permanent buying and selling, accounts receivable, bonus giving, holiday allowance (THR), non-material assistance and family relations. The gold-panning women are still very dependent on the existence of gold boss in selling their panned gold products recalling that the Tombang Wanita Amanah Duo Cooperative still have limited capital and cannot operate as it should.